2022
DOI: 10.1590/s1677-5538.ibju.2021.0495
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of surgical and histopathological results of robot-assisted partial nephrectomy with use of three or four robotic arms: an early series results

Abstract: Objectives: The aim of this study was to evaluate whether criteria exist to guide election between the use the three-or four-arm technique in robotic partial nephrectomy (RPN) instead of just the surgeon's preference. Material and Methods: We performed a retrospective review of 80 patients submitted to RPN from May 2016 to February 2020. The patients were divided into two groups of 40, the fi rst submitted to the surgical procedure with use of three robotic arms and the second with four arms. The group divisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“… ABSTRACT
Purpose: Partial nephrectomies in the salvage setting after ablative or surgical therapy remain challenging cases that are underreported in the literature ( 1 - 5 ). The aim of this video is to demonstrate techniques for robotic salvage partial nephrectomy to manage recurrent renal cell carcinoma (RCC) after failed prior partial nephrectomy and primary cryotherapy.
…”
mentioning
confidence: 99%
“… ABSTRACT
Purpose: Partial nephrectomies in the salvage setting after ablative or surgical therapy remain challenging cases that are underreported in the literature ( 1 - 5 ). The aim of this video is to demonstrate techniques for robotic salvage partial nephrectomy to manage recurrent renal cell carcinoma (RCC) after failed prior partial nephrectomy and primary cryotherapy.
…”
mentioning
confidence: 99%
“…Dr. Schulze and colleagues from Brazil performed in page 493 an important report about robotic surgery (7). The authors evaluated whether criteria exist to guide election between the use the three-or four-arm technique in robotic partial nephrectomy (RPN) instead of just the surgeon's preference and concluded that the two robotic partial nephrectomy techniques had similar oncological and postoperative outcomes, with minimal perioperative complications.…”
mentioning
confidence: 99%